Estimating EC and ionic EC contribution percentage of nutrient solution based on ionic activity - Song, Jinxiu; Xu, Lin; He, Dongxian; Tuskagoshi, Satoru; Kozai, Toyoki; Shinohara, Yutaka (International Journal of Agricultural and Biological Engineering, 2019)
The dynamic monitoring technology of inorganic ions using ion selective electrodes has some problems such as low precision, vulnerability to other ions, short service life, and high price. Due to the difficulty of dynamic control based on ionic concentration of nutrient solution, EC and pH values of nutrient solution are often used as feedback control indexes in hydroponic system. In this study, estimation algorisms of EC and ionic EC contribution percentage based on ionic activity were proposed to understand the quantitative relationship between ionic concentration and EC. With a view to predicting the EC accurately by mean ionic activities of specific salts in nutrient solution based on a specific formula, ionic concentration could also be calculated by the actual measurement of EC combined with ionic EC contribution percentage. With Japanese horticultural experimental nutrient formula and Yamasaki tomato nutrient formula, significant linear correlations between estimated EC and measured EC were found with determination coefficients over 0.99. Ionic EC contribution percentage was not affected by different relative concentrations of nutrient solutions. However, ionic EC contribution percentage changed significantly when adding specific salts with different concentrations, and different changes were found in each anions and cations of specific salt added. When the same K+ concentration was added in different forms of KNO3, K2SO4, KCl, and KH2PO4, the changes of ionic EC contribution percentage of K+ were similar, but those of other anions in potassium salts varied greatly. The relative errors of estimated EC of nutrient solutions based on ionic activities were only 1.3% in horticultural experimental nutrient solution and 1.8% in Yamasaki tomato nutrient solution with different relative concentrations compared to measured EC. The relative errors of estimated EC of nutrient solutions with specific salt added were only 0.1%-0.5% compared to measured EC in two nutrient solution. Therefore, the dynamic feedback control of ionic concentration of nutrient solution could be realized by using EC measurement combined with ionic EC contribution percentage to improve the ionic quantitative control in nutrient solution. The EC control of nutrient solution in automatic irrigation system might be upgraded to ionic concentration control by using algorisms above of ionic EC contribution percentage and EC estimation to meet dynamic demands of hydroponic crops for ionic concentration in different growth stages.Keywords: hydroponics, nutrient solution, ionic activity, soilless culture, Debye-Hückel limiting equation, ionic EC contribution percentage, nutrient formula, solution dynamic controlDOI: 10.25165/j.ijabe.20191202.4399Citation: Song J X, Xu L, He D X, Tuskagoshi S, Kozai T, Shinohara Y. Estimating EC and ionic EC contribution percentage of nutrient solution based on ionic activity. Int J Agric & Biol Eng, 2019; 12(2): 42–48.